2013
DOI: 10.1136/bjsports-2013-092192
|View full text |Cite
|
Sign up to set email alerts
|

London 2012 Paralympic swimming: passive drag and the classification system

Abstract: Although swimmers with the lowest swimming class experienced the highest passive drag and vice versa, the inconsistent difference in mean passive drag between adjacent classes indicates that the current classification system does not always differentiate clearly between swimming groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 18 publications
(22 reference statements)
5
49
0
Order By: Relevance
“…[9][10][11][12][13] Para swimmers with limb deficiency, resulting from trauma or congenital birth defect, have reduced body surface area that impacts their ability to produce propulsive forces and minimize their resistance in the water. [14][15][16] The current classification system uses direct limb length measurements and body segment parameters (in cases of bilateral impairments) to determine the relative length of para swimmers' affected limb segments and summate a points score used for classification. 3 Points are allocated for the hand, forearm, upper arm, foot, shank, and thigh based on each limb segments' expected contribution to performance in the swimming strokes of the S and SB classes.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] Para swimmers with limb deficiency, resulting from trauma or congenital birth defect, have reduced body surface area that impacts their ability to produce propulsive forces and minimize their resistance in the water. [14][15][16] The current classification system uses direct limb length measurements and body segment parameters (in cases of bilateral impairments) to determine the relative length of para swimmers' affected limb segments and summate a points score used for classification. 3 Points are allocated for the hand, forearm, upper arm, foot, shank, and thigh based on each limb segments' expected contribution to performance in the swimming strokes of the S and SB classes.…”
mentioning
confidence: 99%
“…15 This is 300 because large correlations were found between free-swim velocity and the International Point (Table 3). 11 However, as the mean difference in drag between classes was found 313 to be inconsistent, it was concluded that the current classification system does not always 314 differentiate clearly between swimming groups. 11 …”
mentioning
confidence: 99%
“…3,14,22,24,25,29 Also, biomechanics were important in evidence-based 98 classification in Paralympic sports (n=6; some studies addressed more than one of these 99 points) (Tables 1-3). 5,6,10,11,17,32 In the current review, sports were subdivided into three main 100 groups based on Bernardi et al …”
mentioning
confidence: 99%
See 2 more Smart Citations